Metalloprotease Meprin β Generates Nontoxic N-terminal Amyloid Precursor Protein Fragments in Vivo - Jefferson, Tamara (American Society for Biochemistry and Molecular Biology, 2011)
Identification of physiologically relevant substrates is still the most challenging part in protease research for understanding the biological activity of these enzymes. The zinc-dependent metalloprotease meprin β is known to be expressed in many tissues with functions in health and disease. Here, we demonstrate unique interactions between meprin β and the amyloid precursor protein (APP). Although APP is intensively studied as a ubiquitously expressed cell surface protein, which is involved in Alzheimer disease, its precise physiological role and relevance remain elusive. Based on a novel proteomics technique termed terminal amine isotopic labeling of substrates (TAILS), APP was identified as a substrate for meprin β. Processing of APP by meprin β was subsequently validated using in vitro and in vivo approaches. N-terminal APP fragments of about 11 and 20 kDa were found in human and mouse brain lysates but not in meprin β(−/−) mouse brain lysates. Although these APP fragments were in the range of those responsible for caspase-induced neurodegeneration, we did not detect cytotoxicity to primary neurons treated by these fragments. Our data demonstrate that meprin β is a physiologically relevant enzyme in APP processing.